Cationic Diazapentacenium Polymers Made in a Sequence of CN Cross Coupling Polymerization and Acid‐Mediated Postpolymerization Cyclization. Issue 19 (17th July 2021) - Wetterling, Dario; Forster, Michael; B. Rodrigues, Ana Clara; Seixas de Melo, J. Sérgio; Scherf, Ullrich
Abstract: Polycationic stepladder polymers containing 5, 12‐diazapentacenium bistriflate repeat units are made in a two‐step sequence of a carbon‐nitrogen cross coupling polymerization and subsequent postpolymerization cyclization. The deeply colored products show a rather weak conjugative interaction between the dicationic diazapentacenium repeat units along the polymer chains. Abstract : Polycationic stepladder polymers with 5, 12‐diazapentacenium bistriflate repeat units are made in a sequence of cross‐coupling polymerization and postpolymerization cyclization. The polyelectrolytes show an only moderate electronic coupling between the polycyclic repeat units.